Trigonal distortion in the Kitaev candidate honeycomb magnet BaCo2 (AsO4)2 - Ferreira-Carvalho, Miguel; Rößler, S.; Chang, C. F.; Hu, Z.; Valvidares, S. M.; Gargiani, P.; Haverkort, Maurits W.; Mukharjee, Prashanta K.; Gegenwart, P.; Tsirlin, A. A.; Tjeng, L. H. (Physical review, 2025)
We conducted x-ray absorption (XAS) and magnetic circular dichroism (XMCD) measurements at the Co 𝐿2,3 edges on single crystals of the Kitaev candidate honeycomb lattice compound BaCo2⁢(AsO4)2. The measurements employed the inverse partial fluorescence yield technique, which is ideal for acquiring reliable x-ray absorption spectra from highly insulating samples, enabling precise quantitative analysis. Our experimental results revealed a significant linear dichroic signal, indicating strong trigonal distortion in the CoO6 octahedra in BaCo2⁢(AsO4)2. We performed a detailed analysis of the experimental XAS and XMCD spectra using a full-multiplet configuration-interaction cluster model. This analysis unveiled that the 𝑡2⁢𝑔 hole density is predominantly localized in the 𝑎1⁢𝑔 orbital. Through XMCD sum rules and theoretical calculations, we quantified both the spin and orbital magnetic moments. Our study demonstrates that the local electronic structure of the CoO6 octahedra displays an effective trigonal distortion of approximately −0.114 eV. This distortion is larger than the Co 3⁢𝑑 spin-orbit coupling constant, emphasizing the crucial impact of local structural distortions on the electronic and magnetic properties of BaCo2⁢(AsO4)2.
Im Titel sind die Zahlen "2" und "4" jeweils tiefgestellt
Gesehen am 03.02.2026